Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.698
|View full text |Cite
|
Sign up to set email alerts
|

Negated and Misprimed Probes for Pretrained Language Models: Birds Can Talk, But Cannot Fly

Abstract: Building on Petroni et al. (2019), we propose two new probing tasks analyzing factual knowledge stored in Pretrained Language Models (PLMs). (1) Negation. We find that PLMs do not distinguish between negated ("Birds cannot [MASK]") and non-negated ("Birds can [MASK]") cloze questions. (2)Mispriming. Inspired by priming methods in human psychology, we add "misprimes" to cloze questions ("Talk? Birds can [MASK]"). We find that PLMs are easily distracted by misprimes. These results suggest that PLMs still have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 21 publications
14
158
0
Order By: Relevance
“…Yet, for some reason the cook's eyes did not water". While the LM recognizes the lexical relatedness between onions and watering eyes, it is not sensitive to negation, as was recently shown for several other language models (Ettinger, 2020;Kassner and Schütze, 2020).…”
Section: Disconfirmed Expectationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Yet, for some reason the cook's eyes did not water". While the LM recognizes the lexical relatedness between onions and watering eyes, it is not sensitive to negation, as was recently shown for several other language models (Ettinger, 2020;Kassner and Schütze, 2020).…”
Section: Disconfirmed Expectationsmentioning
confidence: 70%
“…On the one hand, Petroni et al (2019) and Davison et al (2019) somewhat successfully used pre-trained LMs to complete commonsense KBs. On the other hand, Logan et al (2019) have shown that LMs are limited in their ability to generate accurate factual knowledge, and Kassner and Schütze (2020) and Ettinger (2020) pointed out that LMs are not sensitive to negation, resulting in generating incorrect facts ("birds can't fly"). Finally, Shwartz et al (2020b) showed that despite being noisy, knowledge generated by LMs can be used to improve performance on commonsense tasks.…”
Section: Related Workmentioning
confidence: 99%
“…While both works have shown somewhat promising results, other work showed that knowledge extracted from LMs is expectantly not always ac-curate. Specifically, Kassner and Schütze (2020) showed that negated facts are also considered likely by the LM, while Logan et al (2019) pointed out that LMs may over-generalize and produce incorrect facts such as "Barack Obama's wife is Hillary".…”
Section: Extracting Knowledge From Lmsmentioning
confidence: 99%
“…Despite the performance boost, LMs as knowledge providers suffer from various shortcomings: (i) insufficient coverage: due to reporting bias, many trivial facts might not be captured by LMs because they are rarely written about (Gordon and Van Durme, 2013). (ii) insufficient precision: the distributional training objective increases the probability of non-facts that are semantically similar to true facts, as in negation ("birds cannot fly"; Kassner and Schütze, 2020). LMs excel in predicting the semantic category of a missing word, but might predict the wrong instance in that category (e.g., depending on the phrasing, BERT sometimes predicts red as the color of a dove).…”
Section: Introductionmentioning
confidence: 99%
“…For example, our model predicts 'climate change' is an attributing factor in the comment 'there is no proof of climate change droughts and floods are all natural phenomenon they have happened before there were humans also' with high confidence. Our model fails to understand the negation as well as the context; perhaps due to a well-documented limitation of BERT's inability in handling negation (Kassner and Schütze, 2019).…”
Section: Error Analysismentioning
confidence: 97%